2005
DOI: 10.2298/hel0542107b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging process on biochemical changes in sunflower seed

Abstract: This investigation was conducted in order to determine the degree of biochemical changes during accelerated and natural aging of sunflower seed. Five sunflower lines developed in Novi Sad, submitted to accelerated aging for three and five days, and natural aging of six and twelve months under conventional storage and controlled conditions, were used in these trials. Malondialdehyde, superoxide dismutase contents and peroxidase activities were studied. Lipid peroxidation and superoxide dismutase and peroxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
7
31
1
4
Order By: Relevance
“…The results of these studies confirm the earlier reports that the increase in the lipid peroxidation during storage is associated with a corresponding decrease in the activity of peroxidase and catalase (Sharma et al 2005(Sharma et al , 2006Zhang and Kirkham 1996;Balesevic-Tubic et al 2005).The inhibition of free radical and peroxide scavenging enzymes may result in an increase in MDA level (Sung 1996;Sharma et al 2005). Several investigations have indicated that free radical induced lipid peroxidation can damage cell membranes and are likely to be primary cause of deterioration of aged seeds (Ponquett et al 1992).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The results of these studies confirm the earlier reports that the increase in the lipid peroxidation during storage is associated with a corresponding decrease in the activity of peroxidase and catalase (Sharma et al 2005(Sharma et al , 2006Zhang and Kirkham 1996;Balesevic-Tubic et al 2005).The inhibition of free radical and peroxide scavenging enzymes may result in an increase in MDA level (Sung 1996;Sharma et al 2005). Several investigations have indicated that free radical induced lipid peroxidation can damage cell membranes and are likely to be primary cause of deterioration of aged seeds (Ponquett et al 1992).…”
Section: Resultssupporting
confidence: 88%
“…These FFA are subjected to lipoxygenase leading to the formation of hydroperoxides (St Angelo and Ory 1983) and ultimately result in the accumulation of MDA (Robert et al 1980). Thus in oilseeds such as soybean and sunflower, autooxidation of lipids and increase in the content of FFA during storage are the main reasons for rapid deterioration of seeds (Balesevic-Tubic et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer seeds storage period increases intensity of seeds ageing [10]. These results are in good agreement with many researchers [5,7,12,13,15,17,19].…”
Section: Moisture Percentage (%)supporting
confidence: 91%
“…In soybean, auto oxidation of lipids and increased content of free fatty acids during storage period are the main reasons for rapid deterioration of oil seed crop as announced by Balasevic-Tubic et al (2005). Free fatty acid content was the highest in control among the treatments.…”
Section: Resultsmentioning
confidence: 99%